Behavior of hexagonal multicell CFST columns under lateral cyclic loads: Experimental study. (1st March 2021) - Yin, Fei; Cao, Wan-Lin; Wang, Ru-Wei; Peng, Bin; Dong, Hong-Ying
Highlights: Experimental study of eight hexagonal multicell CFST columns were conducted. The effects of various parameters to hexagonal multicell CFST columns were analysed. A FBM model was established considering the differences among the different cells. Several stress-strain relationships of concrete and codes were were discussed. Abstract: Multicell concrete-filled steel tubulars (MCFSTs) have been widely utilized in super-high-rise buildings. Hexagonal six-cell CFST columns have received attention from scholars, and a series of investigations have been conducted. However, investigations on their behavior under lateral cyclic loads are rare. Hence, 8 samples were designed, and an experimental study was conducted under lateral cyclic loads. The parameters included 3 loading directions (strong axis, 45 degrees, and weak axis), 2 axial loads (750 kN and 1500 kN), and 2 types of cross-sectional structures (angle steel-reinforced type and basic type). Analysis was conducted on bearing capacity, the failure mode, ductility, residual deformation, accumulated energy dissipation and strain development. The experimental results indicate that the angle steel can decrease the residual deformation and improve the accumulated energy dissipation and bearing capacity of samples. The performances of samples under different loading directions were significantly different. With the loading directions changing from the strong axis to the weak axis, the accumulated energy dissipation and bearing capacity decreased. The influence of the axial load ratio was related to the loading direction. A calculation model using the fiber-based method was established considering the differences among the different cells. According to the calculation results of this method, the limit axial load ratio decreased with the loading directions changing from the strong axis to the weak axis. The stress-strain relationships of plain concrete and confined concrete based on single-cell CFSTs were conservative in predicting the F - Δ curves, and the error increased with an increasing axial load ratio, while the separation model showed the best agreement.